Implementing Regional Trade Agreements with Environmental Provisions A Framework for Evaluation - Gallagher, Peter (OECD Trade and Environment Working Papers, 2011)
This document sets out a framework for evaluating the implementation of environmental provisions in Regional Trade Agreements. The checklist approach to the evaluation of countries' experience of implementation complements the OECD's Checklist for Negotiators (2008). Among the issues addressed are institutional arrangements, co-operation, capacity building, public participation, resolution of differences and assessment